ナンキョク ミズホ コウゲン ノ ユキ ノ サンソ ドウイタイ ソセイ - 加藤, 喜久雄; カトウ, キクオ; 渡辺, 興亜; ワタナベ, オキツグ; 佐藤, 和秀; サトウ, カズヒデ; KATO, Kikuo; WATANABE, Okitsugu; SATOW, Kazuhide (国立極地研究所, 1977)
P(論文) 昭和基地およびみずほ観測拠点における降雪および飛雪と,内陸トラバースルートに沿った地点での雪,2mピットの雪について,酸素同位体組成を測定し,それが何により規制されているか検討した.昭和基地における雪のδ^<18>O値の変動は,沿岸低気圧によりもたらされる水蒸気の吹き込みとよく相関している.雪のδ^<18>O値の季節変化は,昭和基地においてもみずほ観測拠点においても,気温の変化のみによって規制されていない.トラバースルートに沿った地点で採取した雪のδ^<18>O値に,著しい増大が見られる地域が見出された.この地域は,沿岸低気圧と南極高気圧が大きく影響している二つの気候区の境に当たり,この境は季節により変化しているものと考えられる. Oxygen isotopic composition of snow samples taken on different dates at Syowa Station and Mizuho Camp, and at various stations during the traverses of the 15th Japanese Antarctic Research Expedition in 1974-1975 was determined. Daily variation of oxygen isotopic composition of snow at Syowa Station is caused mainly by the supply of ^<18>O-rich water vapor on account of the approach of a depression. Seasonal variation of oxygen isotopic composition of snow at Syowa Station and Mizuho Camp is not always controlled only by the temperature of formation of the snow. An anomaly in oxygen isotopic composition of snow sampled at the stations along the traverse routes was found. The area where the anomaly was found is considered to be the boundary between the spheres of influence of Antarctic high and coastal low atmospheric pressure. departmental bulletin paper